Yellow Wine Polyphenolic Compounds Inhibit Matrix Metalloproteinase-2, -9 Expression and Improve Atherosclerotic Plaque in LDL-Receptor-Knockout Mice - Xiaoya Zhai; Jufang Chi; Weiliang Tang; Zheng Ji; Fei Zhao; Chengjian Jiang; Haitao Lv; Hangyuan Guo (Elsevier, 2014)
Abstract.: Many epidemiological studies have strongly suggested an inverse correlation between dietary polyphenol consumption and reduced risks of cardiovascular diseases. Yellow rice wine is a Chinese specialty and one of the three most ancient wines in the world (Shaoxing rice wine, beer, and grape wine). There is a large amount of polyphenol substances in yellow rice wine. This experiment was designed to study the potential beneficial effects of yellow wine polyphenolic compounds (YWPC) from yellow rice wine on progression of atherosclerosis in vivo and to further explore its underlying mechanisms. Six-week-old male LDL-receptor-knockout mice were treated with high-fat diet to establish the mouse model with atherosclerosis. Animals received 10, 30, or50 mg/kg per day of YWPC or 10 mg/kg per day rosuvastatin or water (vehicle) for 14 weeks. The results indicated that YWPC and rosuvastatin significantly decreased circulating total cholesterol and low-density lipoprotein cholesterol. Compared to the control group, the atherosclerosis lesion area in the rosuvastatin-intervention group and YWPC at doses of 10, 30, and 50 mg/kg per day intervention groups decreased by 74.14%, 18.51%, 40.09%, and 38.42%, respectively. YWPC and rosuvastatin decreased the expression and activity of matrix metalloproteinases (MMP)-2, 9, whereas the expression of the endogenous inhibitors of these proteins, namely, tissue inhibitors of matrix metalloproteinases (TIMP)-1, 2, increased when compared to the control group. It can be concluded that the YWPC is similar to the benefic effects of rosuvastatin on cardiovascular system. These effects may be attributed to their anti-atherosclerotic actions by lowering lipid and modulating the activity and expression of MMP-2, 9 and TIMP-1, 2. Keywords:: yellow wine polyphenolic compound, atherosclerosis, lipid-lowering, matrix metalloproteinase, tissue inhibitor of matrix metalloproteinase